2021
DOI: 10.3390/clinpract11010021
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response Failure in Paucisymptomatic Long-Standing SARS-CoV-2 Spreaders

Abstract: The coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has rapidly spread throughout the world. This disease has a spectrum of different clinical pictures with different outcomes. Herein, we report all the data from three paucisymptomatic patients during a hospital stay that might represent a paradigmatic example of the method by which SARS-CoV-2 is shed. We demonstrated the lack of an adequate qualitative and quantitative immune response by multiparame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In this sense, Iwasaki and Medzhitov showed that the level of IL-6 was markedly higher in severe cases than in mild and moderate cases. Still, the levels of CD4+ T cells, CD8+ T cells, and NK cells were decreased, indicating immunosuppression in severe COVID-19 [ 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, Iwasaki and Medzhitov showed that the level of IL-6 was markedly higher in severe cases than in mild and moderate cases. Still, the levels of CD4+ T cells, CD8+ T cells, and NK cells were decreased, indicating immunosuppression in severe COVID-19 [ 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Adaptive immunity is the key factor in the complete eradication of the virus [ 4 ]; this immune pathway needs 4 to 7 days to be activated after the occurrence of the infection. If an effective adaptive antiviral response is not generated in time to suppress the virus, innate immune responses will potentiate but are unable to effectively eradicate the virus, and this also leads to systemic inflammatory responses with the irrepressible release of inflammatory cytokines [ 75 , 76 , 77 , 78 ]. Elderly patients and those with chronic diseases need a longer period of time to generate adaptive and innate immune responses because of cell senescence.…”
Section: Discussionmentioning
confidence: 99%